Formulation A Review on Recent Success in Cancer Nanomedicine - N.Bodkhe, S.; Gadhave, R.U.; Rothe, S.S.; Sheikh, A.A.; Biyani, K.R. (Asian Journal of Pharmaceutical Research and Development, 2023)
Cancer continues to be one of the most difficult global healthcare problems. Although there is a large library of drugs that can be used in cancer treatment, the problem is selectively killing all the cancer cells while reducing collateral toxicity to healthy cells. There are several biological barriers to effective drug delivery in cancer such as renal, hepatic, or immune clearance. Nanoparticles loaded with drugs can be designed to overcome these biological barriers to improve efficacy while reducing morbidity. The pathological processes of cancer are complex. Current methods used for chemotherapy have various limitations, such as cytotoxicity, multi-drug resistance, stem-like cells growth, and lack of specificity. Nanomedicine plays an important role in these evolving tumor treatment modalities. We discuss how nanomedicine can be combined with these treatment modalities, provide typical examples, and summarize the advantages brought by the application of nanomedicine. This highlights the progress, challenges and opportunities in cancer nanomedicine and discusses novel engineering approaches that capitalize on our growing understanding of tumour biology and nano–bio interactions to develop more effective nanotherapeutics for cancer patients. This review discusses the current use of clinically approved nanomedicines, the investigation of nanomedicines in clinical trials, and the challenges that may hinder development of the nanomedicinesfor cancer treatment.